Thermodynamics of tower-block infernos: effects of water on aluminum fires - Maguire, John F. (2021)
We review the thermodynamics of combustion reactions involved in aluminum fires in the light of the spate of recent high-profile tower-block disasters, such as the Grenfell fire in London 2017, the Dubai fires between 2010 and 2016, and the fires and explosions that resulted in the 9/11 collapse of the World Trade Center twin towers in New York. These fires are class B, i.e., burning metallic materials, yet water was applied in all cases as an extinguisher. Here, we highlight the scientific thermochemical reasons why water should never be used on aluminum fires, not least because a mixture of aluminum and water is a highly exothermic fuel. When the plastic materials initially catch fire and burn with limited oxygen (O2 in air) to carbon (C), which is seen as an aerosol (black smoke) and black residue, the heat of the reaction melts the aluminum (Al) and increases its fluidity and volatility. Hence, this process also increases its reactivity, whence it rapidly reacts with the carbon product of polymer combustion to form aluminum carbide (Al4C3). The heat of formation of Al4Cl3 is so great that it becomes white-hot sparks that are similar to fireworks. At very high temperatures, both molten Al and Al4C3 aerosol react violently with water to give alumina fine dust aerosol (Al2O3) + hydrogen (H2) gas and methane (CH4) gas, respectively, with white smoke and residues. These highly inflammable gases, with low spontaneous combustion temperatures, instantaneously react with the oxygen in the air, accelerating the fire out of control. Adding water to an aluminum fire is similar to adding "rocket fuel" to the existing flames. A CO2-foam/powder extinguisher, as deployed in the aircraft industry against aluminum and plastic fires by smothering, is required to contain aluminum fires at an early stage. Automatic sprinkler extinguisher systems should not be installed in tower blocks that are at risk of aluminum fires.